US agricultural and forest carbon sequestration over time: An economic exploraration - Heng-Chi Lee; Bruce A. McCarl (The University of Western Ontario, Department of Economics, 2004)
Global average temperature rose 1°F in the last 100 years allegedly due to increasing greenhouse gas concentrations in the atmosphere. In reaction, global society is moving toward coordinated action to reduce manmade greenhouse gas emissions in an effect to avoid possible future adverse effects. Under such an effort, high cost strategies may be required to deal with near term fossil fuel consumption until new technological developments reduce fossil fuel dependency or increase energy utilization efficiency. However, carbon sequestration in the agricultural and forest sectors may serve as an important bridge to the future helping to hold costs down until technology develops. We examine the dynamic role of carbon sequestration in the agricultural and forest sectors can play in mitigation. A 100 year mathematical programming model, depicting U.S. agricultural and forest sectoral activities including land transfers and greenhouse gas consequences is applied to simulate potential mitigation response. The results reveal that carbon sequestration is a very important mitigation strategy that can be implemented in the early decades, although policy design must consider that the stored carbon saturates and in turn could be released in the future.
Keywords: Q54; Q58; 330; climate change mitigation; agriculture and forestry; carbon sequestration; saturation